THE EFFECT OF THE MA’HAD AL-JAMI’AH ACADEMIC COMPETENCY IMPROVEMENT PROGRAM ON AQIDAH, WORSHIP, AND MORALS OF STUDENTS - Dani Fatus Sariroh (Intelegensia : Jurnal Pendidikan Islam, 2021)
The program to improve the academic competence of Ma’had Al-Jami’ah is a series of activities in Ma’had and must be followed by all students of Ma’had Al-Jami’ah IAIN Tulungagung to improve academic abilities, namely the development of religious and linguistic knowledge, and tradition of religious spirituality. The purpose of the research to know the implementation and the effect of the Ma’had Al-Jami’ah Academic Competency Improvement Program towards aqidah, worship, and morals in students. The research method used is an explanatory mixed method (qualitative - qualitative). The population numbered 400 mahasantri. The sampling technique used was simple random sampling, and obtained a sample of 170 students. The results of the research is there is the effect of the Ma’had Al-Jami’ah Academic Competency Improvement Program towards aqidah, worship, and morals in students is shown as a percentage of 87.5%. The implementation of the Ma’had Al-Jami’ah academic competency improvement with book study, religious activities, habituation, and control. Practical and theoretical implications of the program to increase the academic competence of ma’had al-jami’ah in order to improve academic abilities, namely the development of religious knowledge, naming and preserving the tradition of religious spirituality, and moral character.